(untitled) (Physical Education, Health and Social Sciences, 2026)
The advent of CRISPR/Cas12a technology has revolutionized precision breeding in cereal crops by enabling targeted editing of promoter regions to generate yield-enhancing alleles. This review explores the molecular advantages of Cas12a over Cas9, including its preference for AT-rich sequences and staggered cleavage patterns, which facilitate tunable gene expression in non-coding regulatory elements. Through case studies in rice, wheat, barley, and maize, we highlight successful applications such as decoupling pleiotropic effects in the IPA1 locus for increased grain yield, optimizing nutrient transporters like OsPHO1;2, and modulating meristem size via the CLAVATA pathway. Technical optimizations, including codon adaptation, intron integration, and multiplexed guides, have achieved mutagenesis efficiencies exceeding 90% in polyploid species. Emerging tools like base and prime editing, coupled with AI-driven promoter design, further enhance regulatory precision and trait stacking. The global market for CRISPR-edited plants is projected to reach 50.1 billion by 2030, driven by evolving regulations favoring non-GMO classifications for simple edits. This paradigm shift toward promoter engineering offers sustainable solutions for food security amid climate challenges, emphasizing quantitative trait modulation over gene knockouts.